Use of a High-Power Laser for Wound Healing: A Case Report - Pereira, Fabio; Ferreira, Marcus; Mendes, Pablo; Rossi, Fabricio; Alves, Mariana; Alves, Bernadete (Journal of Lasers in Medical Sciences, 2020)
Introduction: The use of low-level laser therapy (LLLT) to treat wounds and accelerate tissue healing has been extensively studied in recent years. The aim of this article is to describe a clinical case using an unfocused high-power laser instead of a low-power laser for therapy. Case Report: In the present article, we present the use of a high-power diode laser to treat an extensive knee injury that occurred after surgical treatment for total prosthesis due to border ischemia resulting from prolonged use of autostatic retractors. Conclusion: It is possible to use an unfocused high-power laser at a decreased intensity to accelerate healing as an adjuvant in the treatment of complicated wounds. This procedure results in reduced application time and cost and an excellent tissue response pattern similar to that reported in the literature with low-power lasers.